0)\\t^2-4t+1=0\\D/4=4-1=3\\t_1=2+\sqrt{3} \\ t_2 = 2-\sqrt{3}\\ \\ (\sqrt{2-\sqrt{3}})^x=t \\ \\ 1) (\sqrt{2-\sqrt{3}})^x = 2+\sqrt{3} |* (\sqrt{2+\sqrt{3}})^x\\ 1 = (\sqrt{2+\sqrt{3}})^{x+2}\\x+2=0\\x=-2\\\\2) (\sqrt{2-\sqrt{3}})^x= 2-\sqrt{3}\\x=2 " alt="(\sqrt{2+\sqrt{3}})^x+(\sqrt{2-\sqrt{3}})^x=4 |*(\sqrt{2-\sqrt{3}})^x\\1 + (\sqrt{2-\sqrt{3}})^{2x} =4(\sqrt{2-\sqrt{3}})^x\\(\sqrt{2-\sqrt{3}})^x=t (t>0)\\t^2-4t+1=0\\D/4=4-1=3\\t_1=2+\sqrt{3} \\ t_2 = 2-\sqrt{3}\\ \\ (\sqrt{2-\sqrt{3}})^x=t \\ \\ 1) (\sqrt{2-\sqrt{3}})^x = 2+\sqrt{3} |* (\sqrt{2+\sqrt{3}})^x\\ 1 = (\sqrt{2+\sqrt{3}})^{x+2}\\x+2=0\\x=-2\\\\2) (\sqrt{2-\sqrt{3}})^x= 2-\sqrt{3}\\x=2 " align="absmiddle" class="latex-formula">
Ответ: ±2